Relationship between AQP5 and chemotherapy resistance in colorectal cancer cells and its mechanism - Xiaoyun Yang; Chunhua Zhou; Wencheng Kong; Tongfa Ju; Qi Xie; Xinchun Liu (Discover Oncology)
Abstract Background Previous studies have suggested that AQP5 expression is increased in colorectal cancer tissues and is associated with the progression and prognosis of colorectal cancer. However, there are few studies on the relationship between AQP5 and chemotherapy resistance in colorectal cancer cells and the related mechanisms. Methods In this study, AQP5 overexpression plasmid was transfected into human colorectal cancer cell lines RKO and HCT116, and the effects of AQP5 combined with 5-FU on the proliferation and apoptosis of colorectal cancer cells and the underlying mechanism were investigated by western blotting, MTT assay and flow cytometry. Then, the results of in vitro experiments were verified in vivo using SPF nude mice. Results AQP5 overexpression plasmid transfected significantly increased AQP5 expression in colorectal cancer cell lines, MTT assay showed that AQP5 overexpression promoted the proliferation of colorectal cancer cells. 5-FU inhibited the proliferation of colorectal cancer cells. Overexpression of AQP5 can restore the inhibition of 5-FU to some extent. Flow cytometry showed that AQP5 had no significant effect on apoptosis of colorectal cancer cells. Western blotting experiments showed that the expression level of p-NF-κB protein in AQP5 overexpression group was significantly up-regulated. The results of tumor bearing experiment in nude mice (in vivo) showed that the tumor growth rate of AQP5 overexpression group was faster, and the tumor diameter and body weight of nude mice were significantly increased. After 5-FU treatment, the tumor volume became smaller, and the tumor volume in AQP5 overexpression group was significantly larger than that in control group. Immunohistochemical results showed that the expression level of p-NF-κB was up-regulated and the number of apoptosis was decreased in the 5-FU treatment group with AQP5 overexpression. Conclusion Overexpression of AQP5 can promote the growth of colorectal cancer cells and promote the occurrence of drug resistance, which may be related to NF-κB signaling pathway. AQP5-mediated chemoresistance suggests its potential as a target for RNA-based gene silencing therapies.